Detrimental Effects of Chronic L-Arginine Rich Food on Aging Kidney - Huang, Ji; Ladeiras, Diogo; Yu, Yi; Ming, Xiu-Fen; Yang, Zhihong (Frontiers in Pharmacology, 2021)
The impaired L-arginine/nitric oxide (NO) pathway is a well recognized mechanism for cardiovascular and renal diseases with aging. Therefore, supplementation of L-arginine is widely proposed to boost health or as adjunct therapy for the patients. However, clinical data, show adverse effects and even enhanced mortality in patients receiving long-term L-arginine supplementation. The effects of long-term L-arginine supplementation on kidney aging and the underlying mechanisms remain elusive. Moreover, high protein and high amino acid diet has been thought detrimental for kidney. We therefore investigated effects of chronic dietary L-arginine supplementation on kidney aging. In both young (4 months) and old (18-24 months) mice, animals either receive standard chow containing 0.64% L-arginine or diet supplemented with additional L-arginine (2.46%) for 16 weeks. Inflammation and fibrosis markers and albuminuria are then analyzed. Age-associated increases in TNF-α, IL-1β, and IL-6, VCAM-1, ICAM-1, MCP1, iNOS and macrophage infiltration, collagen expression, and S6K1 activation are observed, which is not favorably affected, but rather further enhanced, by L-arginine supplementation. Importantly, L-arginine supplementation further enhances age-associated albuminuria and mortality particularly in females, accompanied by elevated renal arginase-II (Arg-II) levels. The enhanced albuminuria by L-arginine supplementation in aging is not protected in Arg-II-/- mice. In contrast, L-arginine supplementation increases ROS and decreases NO production in old mouse aortas, which was reduced in Arg-II-/- mice. The results do not support benefits of long-term L-arginine supplementation. It rather accelerates functional decline of kidney and vasculature in aging. Thus, the long-term dietary L-arginine supplementation should be avoided particularly in elderly population.